The Impact of Wastewater on Eco-Spirituality: A Study of the Bishnumati River - Raut, Prakash Bikram (Pashupati Pragya पशुपति प्रज्ञा, 2025)
This research explores the impact of wastewater on the eco-spirituality of the Bishnumati River and its surroundings. Furthermore, this article deals with how such an impact of wastewater disrupts the interconnectedness of both flora and fauna, including human beings. Moreover, this research methodologically applies the Gaia hypothesis and ecosystem theory to unfold the gradual decline of the relationship between eco-spirituality and the Bishnumati River due to the impact of wastewater. Besides, this article questions what factors lead to the anthropocentric view among the residents near the Bishnumati River and how such an insight creates a crisis in the eco-spirituality of this river. Additionally, this research aims to find out the existing eco-spiritual condition of the Bishnumati River and determine whether anthropocentric practices are responsible for wastewater management. Also, this research finds how both anthropocentric activities and mismanagement of wastewater collectively impact the eco-spiritual connection of the Bishnumati River. Furthermore, such an impact gaps the relation between eco-spirituality and the Bishnumati river. In conclusion, this article focuses on restoring the holiness of the Bishnumati River by combining contemporary environmental measures with eco-spirituality.